Arachidonic Acid in the Diet of Captive Yellowtail and Its Effects on Egg Quality. (12th February 2018) - Stuart, Kevin; Johnson, Ron; Armbruster, Lisa; Drawbridge, Mark
Abstract: Marine finfish require long‐chain (LC) polyunsaturated fatty acids (PUFAs) for normal physiological function, and because these LC‐PUFAs cannot be synthesized by the fish, they must be obtained from the diet. Three LC‐PUFAs—arachidonic acid (ARA; 20:4[n‐6]), eicosapentaenoic acid (EPA; 20:5[n‐3]), and docosahexaenoic acid (22:6[n‐3])—are especially important for growth and development of marine fish embryos and larvae. We supplemented ARA in the diet of Yellowtail Seriola dorsalis to determine whether ARA levels have an effect on egg and larval quality. Two experimental diets were offered to replicate groups of Yellowtail held in 10‐m 3 tanks under ambient water temperature and photoperiod conditions. The reference diet (REF‐D; 1.4 g of ARA per 100 g of total fatty acids) was a commercial premix (BioVita Starter Mash; Bio‐Oregon) without ARA supplementation; the ARA diet (ARA‐D; 4.7 g/100 g total fatty acids) was the commercial premix with 1.0% concentrated ARA oil (40% ARA, weight/weight) added. Fish in the REF‐D treatment spawned 53 times during the spawning season for a total of 18.0 million eggs. Fish in the ARA‐D treatment tanks spawned 30 times during the spawning season for a total of 13.0 million eggs. Viability, hatch rates, and egg diameter were all significantly higher in the ARA‐D treatment. Fatty acid analysis of the diets showed a significant increase in ARA in the ARA‐D diet, and that same increase was seen in the resulting eggs. Correspondingly, ARA‐D eggs had a lower EPA : ARA ratio than REF‐D eggs. The supplementation of ARA generated increases in key performance indices, which might have biological significance in a production setting. We additionally demonstrated that Yellowtail will spawn without hormone induction in small (10‐m 3 ) breeding tanks, which facilitates manipulative studies of broodstock nutrition as reported here. These data represent an excellent starting point for dietary refinements in the future.